On the Static Performance of Commercial GaN-on-Si Devices at Elevated Temperatures - Perkins, Samuel; Arvanitopoulos, A.; Gyftakis, K. N.; Lophitis, Neophytos (My University, 2018)
This work provides an experimentally driven comparison between commercialized Gallium Nitride on Silicon (GaN-on-Si) and Silicon (Si) Super Junction (S-J) power devices at elevated temperatures. Elevated temperature experiments were performed to analyze the static performance of the Panasonic PGA26C09DV Enhancement (E-mode) p-GaN layer Gate Injected Transistor (GIT), the Transphorm TPH3206LD, TPH3206PD cascode GaN High Electron Mobility Transistors (HEMTs) and the Infineon SPA15N60C3 Silicon S-J. The Device Under Tests (DUTs) were characterized in a thermal chamber using the B1505A Power Device Analyzer. The elevated temperature measurements were taken; analyzed and compared. The performance of the GaN-on-Si indicated a strong robustness in thermally challenging environments and demonstrated superior performances at higher temperatures in comparison to traditional Si S-J technology.
Keywords: B1505A; cascode GaN; E-mode; GaN HEMT; high temperature; power devices; static performance